Oral hygiene status based on blood types of dentistry students - Deradjat, Arini Puspitasari; Mariam, Marry Siti; Yubiliana, Gilang (Padjadjaran Journal of Dentistry, 2013)
Introduction: Oral hygiene status can be measured by OHI (Oral Hygiene Index) the which is influenced by four factors: environmental, behavioral, hereditary and health services. Plaque and calculus Become an indicator of OHI, roomates poor OHI is one of the main causes of periodontal disease. Blood type as hereditary factors may be a risk factor for periodontal disease. More over, a dental health education will Affect a person’s behavior in dental and oral hygiene. The purpose of this research is to get an overview of the oral hygiene status of dental students in Padjadjaran University (Students in Regular Class 2008) based on blood types as a risk factor for periodontal disease, Methods:This study was a descriptive study with survey technique. Samples were taken with a simple purposive sampling method of 76 respondents, Results:The results Showed that the blood type O shows the best OHI-S with distribution frequency is 94.29% and the worst is blood type B with the distribution frequency is 6.25%, Conclusion: blood type O shows the best OHI-S and blood type B with the worst oral hygiene status is assume in having the biggest risk factor for periodontal disease compare to other blood types.